Tinjauan Sistematis Evidence-Based Practice: Mengkritisi Misinformasi Penolakan Ventilasi Mekanis Melalui Peningkatan Literasi Media dan Komunikasi Keperawatan Kritis - Asriadi Prihandika Widianto; Devi Titik Aprilia; Sudirman Sudirman (Jurnal Ners, 2026)
The infodemic phenomenon in the digital era has triggered the massive spread of misinformation regarding critical medical interventions, particularly the mistaken perception that mechanical ventilation is the cause of death in patients with respiratory failure. This has resulted in family refusal of the procedure, increased mortality, and moral distress among nurses. This study aims to analyze the impact of this misinformation and formulate mitigation strategies through media literacy and nursing communication. This research method is a systematic review based on Evidence-Based Practice (EBP). The literature search was conducted in the Scimago, PubMed, and ScienceDirect databases spanning 2021 to 2026. Inclusion criteria included studies on ventilator misinformation, lung-protective ventilation strategies, and the role of nurses in addressing communication barriers in intensive care units. Results: The analysis showed that ventilator misinformation is rooted in a failure to understand the pathophysiology of Acute Respiratory Distress Syndrome (ARDS) by laypersons. The implementation of lung-protective ventilation has been clinically proven to reduce mortality, but its efficacy is often hampered by conflicts with patient autonomy based on manipulative information. This study identified that the Family-Centered Care (FCC) approach combined with prebunking (psychological inoculation) and empathetic debunking techniques was effective in reducing family resistance. Conclusion: Managing the infodemic in critical care settings requires transforming the role of nurses into digital literacy agents. The use of the SIFT (Stop, Investigate, Find, Trace) method and strengthening therapeutic communication are key to restoring public trust in the healthcare system. Integration of media literacy into the nursing curriculum is highly recommended to equip healthcare workers to face future information challenges